Mortality and infection of wireworm, Agriotes obscurus [Coleoptera: Elateridae], with inundative field applications of Metarhizium anisopliae - Kabaluk, J.; Vernon, Robert; Goettel, Mark (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2007)
In an attempt to cause fatal infection of wireworm Agriotes obscurus [Coleoptera: Elateridae], Metarhizium anisopliae was applied in the field as factorial combinations of conidia formulated as granules at 3.68 g granules or 1.25 x 1010 cfu per 196 cm2 (6.38 x 107 conidia cm-2), as conidia mixed with soil at 1.26 x 1010 cfu per 2.986 cm3 soil (4.22 x 106 conidia cm-3 soil), and as conidia-coated wheat seed (100 wheat seeds or 4.16 x 109 cfu per 196 cm2 = 2.12 x 107 conidia cm-2). The treatments resulted in a significantly greater number of mycosed wireworms compared with the control over and during five sampling periods. Significant differences in total wireworm mortality and mycosed wireworms in the field occurred at any time ranging from 15 to 82 d following treatment. The treatments also caused a reduction in the number of wireworms found in the cores, implying that they had a repellent effect. Latent infection of wireworms became apparent after living wireworms from the field treatments died following incubation under laboratory conditions, in numbers significantly greater than the control. This study showed that M. anisopliae can be applied in the field and infect and kill wireworms, but only at concentrations exceeding 4 x 106 conidia cm-3 with the subject isolate, wireworm species, and field conditions used in this study.